O sacrifício de animais nos rituais de religiões de matriz africana e a liberdade religiosa garantida em lei - Kesselring, Ana Beatriz Marchioni (2023)
The present work is the result of the analysis of the practice of animal sacrifice by religions of African origin and the contemporary discussions on the subject, mainly due to the discussion regarding the legality of this practice, which occurred, at first, within the scope of the State Court of Rio Grande do Sul (ADI/ 70010129690) and continuing, at the Brazilian Supreme Court (RE/494601). Considering the judges and Justices votes in these lawsuits were, in general, restricted to the analysis of legal issues involving the subject of animal sacrifice by religions of African origin (especially the right to protection of animals versus the right to religious freedom), and due to the fact that few votes were based on the scientific literature on the subject, the present study sought to analyze how much knowledge arising from the Science of Religion could have contributed to these judgments. The Science of Religion is adequate to contribute to a better understanding of the subject, since it allows a distanced and rigorous analysis of this religious practice. In the search for scientific answers to the understanding of animal sacrifice in the religious context, through anthropological studies, the understanding was clear that the repudiation of this practice in Brazil is given in a special way to those practiced by religions of African origin and for deeper reasons more related to the existing structural racism in Brazilian society